2019
DOI: 10.1097/mop.0000000000000833
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity as a continuum in primary immunodeficiency

Abstract: Purpose of review Primary immunodeficiency disorders (PIDs) are no longer defined by infections alone. First clinical sign or sequelae of PID may include autoimmunity, such as cytopenias, arthritis or enteropathy. This review addresses the latest in multidisciplinary approaches for expanding clinical phenotypes of PIDs with autoimmunity, including new presentations of known entities and novel gene defects. We also discuss diagnostic tools for identifying the distinct changes in immune cells subsets and autoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 58 publications
0
55
0
2
Order By: Relevance
“…The custom panel includes 46 genes involved in the pathogenesis of agammaglobulinemia, CVID, and IEI immune‐dysregulation disorders (Table 1A/1B) based on the last update of the ESID classification 11,12 …”
Section: Methodsmentioning
confidence: 99%
“…The custom panel includes 46 genes involved in the pathogenesis of agammaglobulinemia, CVID, and IEI immune‐dysregulation disorders (Table 1A/1B) based on the last update of the ESID classification 11,12 …”
Section: Methodsmentioning
confidence: 99%
“…Primary immune regulatory disorders (PIRDs) are a subgroup of IEIs characterized by heterogeneous clinical phenotypes, predominated by autoimmunity, lymphoproliferation, autoinflammation, and malignancy [ 2 , 3 , 4 , 5 ]. These disorders develop from a breakdown in the immune tolerance pathways that can affect different levels of the immune system, modeling various mechanisms for disease development and governing autoimmunity ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in various genes have been associated with these diseases and the prototype disorder is immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) [ 6 , 7 , 8 ], caused by mutations in the Forkhead Box P3 (FOXP3) gene, leading to defective CD4+CD25+ regulatory T-cell (Treg) production and described as a Treg defect (Tregopathies; Table 2 ) [ 9 ]. Additional studies later revealed many different genes that pave the way for reclassification of the patients previously described as having combined immune deficiency (CID) or common variable immunodeficiency (CVID) to monogenic PIRD; some of these cases are also accepted as IPEX- and ALPS-like disorders [ 2 , 7 ]. The presenting symptoms might be quite different than increased frequency of infections and the underlying immune dysregulatory disorders can lead to multiple autoimmunities, lymphoproliferation, and malignancies ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an expanding spectrum of ALPS-like disorders, including caspase 8 deficiency state (CEDS, resulting from a germline mutation in caspase 8 [ CASP8 ]); RAS-associated autoimmune leukoproliferative disease (RALD), resulting from gain of function somatic mutation of the neuroblastoma RAS viral oncogene ( NRAS) or proto-oncogene Kirsten Rat Sarcoma virus ( KRAS) ; X-linked lymphoproliferative syndrome (XLP1) resulting from mutation or deletion of the SH2D1A gene; heterozygous loss of function mutation in nuclear factor kappa light chain enhancer of activated B cells ( NFKB-1 ), heterozygous loss of function mutation of cytotoxic T-lymphocyte associated protein 4 ( CTLA-4 ), and mutations of the FAS -associated protein with death domain (FADD), among others. Approximately one-third of subjects with clinical features of ALPS have unidentified genetic defects ( 1 , 2 , 4 ). Patients with unknown genetic defects but clinical features of ALPS are classified as Dianzani autoimmune lymphoproliferative disease (DALD) ( 2 ).…”
Section: Introductionmentioning
confidence: 99%